Efek pra-perlakuan menggunakan microwave terhadap kandungan lignoselulosa kulit ari jagung - Tasyabilla Attaya; S. Rosalinda (Agroindustrial Technology, University of Trunojoyo Madura, 2025)
Corn is one of the abundant agricultural commodities in Indonesia. This abundant production of corn leaves considerable waste. One of the wastes produced is corn pericarps. Corn pericarps contain lignocellulose, whose utilization has not been studied much. This study aims to determine changes in the lignocellulosic content of corn pericarps in the physico-chemical delignification pre-treatment using electromagnetic waves with microwaves with various solvents NaOH 4% and distilled water. The lignocellulose content was tested using the Van Soest method. The results showed that the raw material for corn pericarps contained 50.4% hemicellulose, 14.6% cellulose, and 0.98% lignin. The results of pre-treatment using a microwave with NaOH 4% solvent produced 14.6% hemicellulose, 33.98% cellulose, and 0.6% lignin, and distilled water yielded as much as 50% hemicellulose, 15.58% cellulose, and 0.8% lignin. The pre-treatment method using microwave can reduce lignin levels by up to 38.78% with NaOH solvent and 18.37% with distilled water. In addition, this pretreatment method can also degrade hemicellulose as much as 71.03% with NaOH solvent and 0.8% with aquadest solvent. Thus, the use of NaOH as a solvent showed a much better ability to delignify and degrade hemicellulose than distilled water.